Effect of fasting on peptic ulcer perforation (TAJ: Journal of Teachers Association, 2018)
Background: Peptic ulcer perforation is a common surgical problem in Bangladesh. For Muslims, the whole of the Ramadan is a time of strictly fasting during day time. Globally near one billion Muslims fast during this month. So it is an opportunity to evaluate the relationship between Ramadan fasting and peptic ulcer perforation. Present study was designed to evaluate the effect of fasting, socioeconomic condition, smoking and inadequate treatment of PUD on peptic ulcer perforation.TAJ 2014; 27(1): 4-9